Improving the Accuracy of Methane Sensor with Dual Measurement Modes Based on Off-Axis Integrated Cavity Output Spectroscopy Using White Noise Perturbation - Ce Yang; Mingming Wen; Chen Chen; Chunguang Li; Jianyu Huang; Laiyong Song; Yu Li (Applied Sciences)
A methane (CH4) sensor based on off-axis integrated cavity output spectroscopy (OA-ICOS) was developed, equipped with two measurement schemes: direct absorption spectroscopy (DAS) and wavelength modulation spectroscopy (WMS). The sensor used an optical resonant cavity composed of two high reflection mirrors (reflectivity > 99%). With a cavity length of 7 cm, an effective optical path length of 10.8 m and a cavity volume of 8.9 mL were achieved. A distributed feedback laser was used to precisely target the CH4 absorption line near 1.6537 µm. Compared with the original system, the cavity mode noise of the CH4 sensor was further reduced by adding white noise perturbations. The white noise perturbations were generated by the broadband random noise from the signal generator. The special customized narrowband RF noise source was not required. The system complexity and cost could be reduced. In DAS mode, the signal-to-noise ratio (SNR) of the OA-ICOS was 16.2 and the minimum detection limit (MDL) was 2.2 ppm at 117 s. In WMS mode, the SNR of the OA-ICOS was 113.9 and the MDL was 1.2 ppm at 106 s. Compared with the results obtained from the WMS mode and DAS mode, the SNR and MDL was improved 7.0 times and 1.8 times, respectively. The proposed sensor system not only enabled high-accuracy trace gas measurement, but also demonstrated strong potential for applications due to its compact design and low cost.